Exhaustion of NK cells and interferon activation in anti-MDA5+ dermatomyositis are associated and determine the development of ILD - Shao, Chenyi; Zhen, Yan; Xia, Nana; Zhang, Xueliang; Yan, Ninghui; Zhou, Mengmeng; Guo, Yiyuan; Tan, Limin; Guo, Qiang (Frontiers in Immunology, 2025)
ObjectivesThis study aimed to investigate the role of natural killer (NK) cell and interferon (IFN) signaling in the peripheral circulation of anti-MDA5+ dermatomyositis (DM) patients, particularly in the context of interstitial lung disease (ILD) development.MethodsPeripheral blood mononuclear cells (PBMCs) from six newly diagnosed, active anti-MDA5+ DM patients (3 with ILD, 3 without ILD) were analyzed using single-cell RNA sequencing (scRNA-seq), focusing on NK cell features. The correlation between serum cytokine levels and ILD severity assessed by HRCT scores was further analyzed. Flow cytometry in an independent cohort validated NK cell apoptosis, and in vitro experiments evaluated IFN-induced apoptosis in NK-92 cells.ResultsScRNA-seq revealed widespread activation of IFN responses in PBMCs from anti-MDA5+ DM-ILD patients, with pronounced upregulation in innate immune cells (e.g., NK cells and monocytes). A reduction in circulating NK cell proportions was observed in ILD patients. Serum levels of cytokines (IL-1β, IL-2, IL-4, IL-5, IL-10, IL-12P70, TNF-α, and IFN-α) positively correlated with the radiologic severity of ILD as quantified by HRCT scores. Flow cytometry confirmed significantly decreased NK cell counts and increased apoptosis in the ILD group. PBMCs from healthy donors exposed to an ILD-like cytokine milieu exhibited upregulated IFN pathway genes (ISG15, MX2, IFIT3), EIF2AK2 (encoding protein kinase R), and apoptosis-related genes (BCL2, BAX2). In vitro, IFN stimulation directly induced apoptosis in NK-92 cells.ConclusionExcessive IFN activation drives NK cell apoptosis in anti-MDA5+ DM-ILD, contributing to NK cell depletion and ILD development. IFN-related biomarkers may serve as valuable indicators for assessing ILD severity in these patients.